Cancionero e imprenta en la red. - RIPOLL, ENRIQUE (Scripta, 2023)
This article takes a tour of the main projects and data warehouses related to medieval poetry and printing that use information technology intensively. This global vision of the collaboration that exists between philology and computer science allows us to observe how medievalists take advantage of the storage and computational capacities of computers to advance their research and disseminate it, which, ultimately, makes it possible to speed up subsequent work.